Neuroimmune cell interactions and chronic infections in oral cancers - D’Silva, Nisha J.; Pandiyan, Pushpa (Frontiers in Medicine, 2024)
Inflammation is a process that is associated with the activation of distal immunosuppressive pathways that have evolved to restore homeostasis and prevent excessive tissue destruction. However, long-term immunosuppression resulting from systemic and local inflammation that may stem from dysbiosis, infections, or aging poses a higher risk for cancers. Cancer incidence and progression dramatically increase with chronic infections including HIV infection. Thus, studies on pro-tumorigenic effects of microbial stimulants from resident microbiota and infections in the context of inflammation are needed and underway. Here, we discuss chronic infections and potential neuro-immune interactions that could establish immunomodulatory programs permissive for tumor growth and progression.